2008
DOI: 10.1016/j.molonc.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin in combination with bortezomib synergistically induced apoptosis in human multiple myeloma U266 cells

Abstract: Growth of multiple myeloma cells is controlled by various factors derived from host bone marrow microenvironments. Interaction between multiple myeloma cells and bone marrow stromal cells (BMSCs) plays an important role in the expression of adhesive molecules and secretion of growth factors involved in multiple myeloma (MM) cell growth, survival, and resistance to anticancer drugs. Recently, the possibility of developing novel anti‐cancer therapeutic strategies targeting both MM cells and MM cell–BMSC interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 17 publications
2
54
0
Order By: Relevance
“…8, B and C), overall simulated profiles reasonably agree with experimental data. Most commonly, exposure-response relationships of protein expression data are sigmoidal in nature (Bharti et al, 2003a,b;Park et al, 2008Park et al, , 2011. For example, the inhibition of pNFkB activity by curcumin is 10% at 1 mM and 40% at 10 mM (Bharti et al, 2003b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8, B and C), overall simulated profiles reasonably agree with experimental data. Most commonly, exposure-response relationships of protein expression data are sigmoidal in nature (Bharti et al, 2003a,b;Park et al, 2008Park et al, , 2011. For example, the inhibition of pNFkB activity by curcumin is 10% at 1 mM and 40% at 10 mM (Bharti et al, 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inhibition of pNFkB activity by curcumin is 10% at 1 mM and 40% at 10 mM (Bharti et al, 2003b). Similarly, cleaved PARP activation is about 1% at 10 mM curcumin but 100% at 50 mM curcumin (Park et al, 2008). It is therefore interesting that, although our model was developed using a single drug concentration and simple linear coefficients (e.g., S m_M1B and S m_PARP in Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a few smaller trials have studied other interventions with benign side effect profiles aimed at limiting the progression of SMM or MGUS, including anakinra, a targeted IL-1 receptor antagonist 69 ; curcumin, a traditional Indian spice with preclinical antimyeloma activity [70][71][72][73] ; and bisphosphonates, believed to block the initial formation of lytic lesions and alter the BM microenvironment (Table 3). 74,75 For example, in 2008, a randomized study compared zoledronic acid versus surveillance in SMM and demonstrated reduced skeletal events in the treatment arm (zoledronic 55.5% vs surveillance 78.3%; P ϭ .041); however, there was no difference in median time to progression (P ϭ .83) to full-blown multiple myeloma.…”
Section: Development Of Early Treatment Strategiesmentioning
confidence: 99%
“…The THQ value is a dimensionless index of risk associated with long term exposure to chemicals based upon reference upper safe limits. A limited number of THQ investigations have been reported in foodstuffs with the focus being on estimating health risks associated with exposure to heavy metals found in seafoods, and in one case breast milk [14][15][16][17][18][19][20]. Calculations of THQ values for seafoods are apposite as many species accumulate heavy metals and other pollutants in their tissues.…”
Section: Introductionmentioning
confidence: 99%